Gnawing Between Cells and Cells in the Immune System: Friend or Foe? A Review of Trogocytosis - Zhao, Siyu; Zhang, Lichao; Xiang, Suoyu; Hu, Yunyi; Wu, Zhongdao; Shen, Jia (Frontiers in Immunology, 2022)
Trogocytosis occurs when one cell contacts and quickly "bites" another cell and is characterized by contact between living cells and rapid transfer of membrane fragments with functional integrity. This phenomenon was first explained as a mechanism by which amoeba protozoa killed host cells. Interestingly, it has been reported that trogocytosis is involved in various physiological processes, such as the development and regulation of the nervous system, sperm-egg fusion, and embryo development. Moreover, an increasing number of studies have shown that trogocytosis plays an important role in the immune system and the occurrence of relevant diseases. Thus, whether trogocytosis is a friend or foe of the immune system is puzzling, and the precise mechanism underlying trogocytosis has not yet been fully elucidated. Here, we provide an integrated view of the acquired findings of the connections between trogocytosis and the immune system.